STUDY OF POTENTIAL DRUG INTERACTIONS IN HYPERTENSION PATIENS AT THE INPATIENT INSTALLATION OF PERMATA CIREBON HOSPITAL - Risa Deviani Azzahra; Nur Rahmi Hidayati; Indah Setyaningsih; Sulistiorini Indriaty; Lela Sulastri; Nina Karlina (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Identification of drug interactions in hypertensive patients needs to be performed because they affect the achievement of therapeutic effects and can increase the risk of side effects. This study aimed to determine patient characteristics (age, gender, drug items used, and comorbidities), the potential for drug interactions in hypertensive patients, the severity of potential drug interactions, and the type and number of drugs that interact in hypertensive patients at the time of installation. Inpatient at Permata Cirebon Hospital. The sample in this study included patients diagnosed with hypertension at the Inpatient Installation of Permata Cirebon Hospital in 2022 who met the inclusion criteria. This was a descriptive analytical study with retrospective data on patient characteristics (age, sex, drug items used, and comorbidities). The results were analyzed in the form of an overview of potential drug interactions using the Medscape application in the form of percentages and tables. The results of the study of 264 samples of hypertension patients taken by random sampling obtained for drug interaction based on severity events were as many as 149 patients (56,44%) with the highest number of gender, namely women as many as 154 patients (58,33%), the level of severity at most, namely monitors as many as 261 events (82,33%). The most interacting drug was Amlodipine with Metformin, with 27 monitored interactions (8,52%). Drug interactions can occur due to the number of drug therapies used and the presence of comorbidities. Keywords: Hypertension, Drug Interactions, Permata Cirebon Hospital.